Inhibition of Thrombin by Antithrombin III and Heparin Cofactor II In Vivo - Liu, Longbin; Dewar, Lori; Song, Yingqi; Kulczycky, Myron; Morris, Blajchman A; Fenton, John W; Andrew, Maureen; Delorme, M; Ginsberg, Jeffrey; Preissner, Klaus T; Ofosu, Frederick A (Thrombosis and Haemostasis, 1995)
The critical role of thrombin in the pathogenesis of venous and arterial thrombosis, and the effectiveness of glycosaminoglycans as antithrombotic drugs are well known. Antithrombin III is a major inhibitor of thrombin and augmentation of its inhibitory actions by heparin is the basis for the clinical uses of heparin. Recent clinical and experimental studies have demonstrated that another glycosaminoglycan, dermatan sulfate, is an effective antithrombotic drug. Dermatan sulfate catalyses the inhibition of thrombin by heparin cofactor II. The concentrations of heparin cofactor II are higher in the plasmas of individuals with congenital antithrombin III deficiency and pregnant women than controls. The role of heparin cofactor II as a physiologic thrombin inhibitor is unknown. Enzyme-linked immunosorbent assays were used to quantify thrombin-heparin cofactor II and thrombin-antithrombin III endogenous to the plasmas of adult antithrombin III-Hamilton deficient subjects, their siblings with normal antithrombin III levels, pregnant women at term and 3 to 5 days after delivery. Both thrombin-antithrombin III and thrombin-heparin cofactor II complexed with vitronectin were detected in all the plasmas. Significantly, the concentrations of thrombin-heparin cofactor II-vitronectin were higher in the plasmas of congenital antithrombin III deficient subjects and in pre- and post-delivery plasmas than those of normal subjects. In addition, the concentrations of thrombin-heparin cofactor II decreased 3 to 5 days after delivery, reflecting the disappearance of the catalytically active dermatan sulfate elaborated by the placenta. Thus, heparin cofactor II normally inactivates thrombin in vivo, with its role increasing in conditions associated with high levels of heparin cofactor II and/or dermatan sulfate.